Compreensão do planejamento por enfermeiros das equipes da estratégia saúde da família - Oliveira, Conrado Augusto Ferreira de (2015)
The Unified Health System (SUS), in its institutional organization has decentralization policy and the creation of health districts and / or the municipalization of health services by Law 8080, September 1990. Decentralizing the management and services health requires increased operation and decisions at the local level power, for proposed changes in services and effective changes in health care. In order to articulate the current reality with health strategies and health actions in the medium and long term, and through the ability to conduct a situational and systematic calculation, planning emerges as the main tool to support current health policies. Given the plurality of modes of planning by health teams of the family, this study aimed to identify how it's performed by the Planning Family Health Teams, the main potentialities and challenges faced by the teams, how they are organized in its realization and with that encouragement of municipal managers. It is field research, carried out through the qualitative research methodology, whose setting was the city of Uberlândia-MG. The data was collected through semi-structured interviews that took place between May and September 2014. The analysis and interpretation of qualitative material were carried out by content analysis technique proposed by Bardin (2000). The results show that teams consider accomplish in your daily planning, despite the difficulties they face as embezzlement of team members, and territorial population above recommended. Understanding the planning of the coordinators of the teams approaches in most accounts of what is proposed in the strategic and participatory planning, however, it is clear that this understanding is retained in the theoretical field, and little is approaching practical reports of the teams. Specifically on the popular participation in the planning, neither team surveyed pointed to community participation in the planning of actions and services. In some findings can already identify recent changes proposed by the current Municipal Health Plan (SMP). For municipal management can achieve the proposed objectives PMS, there is still a long way to go, which arguably involves the construction of strategic and participatory planning by the Family Health Teams, so that it can improve the efficiency and effectiveness of their actions and contribute significantly to improving the health status of the population. We point out three paths that can strengthen the planning of health teams of the municipal family: the expansion of municipal support in planning teams in addition to the reports and health indicators; establishing methods that can support the coordinators and their teams in the construction and implementation of planning; stimulating popular participation / social control in the preparation of participatory planning. It is understood that other studies in this area may show new ways to strengthen planning for the qualification of actions and proposals of services in partnership with the population and municipal management, contributing to greater resolution for improving access and quality of life communities under their responsibility.